Avaliação do impacto de mutações na região C-terminal da proteína rLID1, uma esfingomielinase do veneno da aranha Loxosceles intermedia, em sua atividade enzimática - Lucas Passos Barreto (2017)
In Brazil, during the year 2015 (last available data), there were 106,983 cases of accidents with venomous animals. Of this total, 19,495 involved spiders (18.22%). The state of Minas Gerais had the highest number of accidents with venomous animals reported with 19,474 recorded cases, of which 2,269 were with spiders (11.6%). Among the accidents with Spider, the genus Loxosceles (brown spider) stands out, responsible for 58% of the spider accidents in which the species was identified. In the world, about 100 different species of Loxosceles have been identified, of which 10 are found in Brazil. The species of major medical importance are: L. intermedia, L. gaucho, L. similis and L. laeta. The venom of the brown spider has an extremely complex composition, containing several toxins. Among the enzymes were identified: hydrolases, hyaluronidases, lipases, peptidases, collagenases, alkaline phosphatase, 5-ribonucleotidase, phosphohydrolases and proteases. Although probably all the enzymes present in the venom are able to contribute in some way to the progression of the injury resulting from the accident, only sphingomyelinases D (SMase D), a lipase present in the venom, were able to produce dermonecrotic lesions, hemolysis and platelet aggregation In laboratory animals. It has been demonstrated in the laboratory that SMase D has several substrates and although it has been demonstrated that in physiological medium the SMase D of L. laeta is capable of releasing choline from lysophosphatidylcholine (LPC), an immunosin- guishing molecule derived from phosphatidylcholine (PC), thus generating lysophosphatidic acid (LPA), known to induce various biological and pathological responses, the mechanism of SMAse D causing dermonecrosis is still not fully elucidated. Recently, a well conserved motif was identified in the C-Terminal portion of SMasesD (ATXXDNPW) of different species and genera, shortly after the last -helix of the TIM barrel ( / )8. Thus, the objective of this work was to evaluate the effects of the conserved D277 and W280 amino acid mutation on the C-terminal portion of the rLID1 sphingomyelinase from the Loxosceles intermedia venom. The recombinant proteins rLID1, rLID1_D (D277A), rLID1_W (W280A) and rLID1_DW (D277A and W280A) were submitted to modeling and molecular dynamics in order to evaluate the impact of mutations in silico. The mutations were found to increase the flexibility of the protein's catalytic loop. After in silico evaluation, the proteins were expressed in BL21 (DE3) Arctic Express, however, only the rLID1, rLID1_D and rLID1_W proteins were soluble. Soluble proteins were purified using affinity chromatography and then, gel filtration chromatography. After obtaining the purified proteins, the enzymatic assay was performed to evaluate the activity of the proteins and it was observed that the mutant rLID1_D has enzymatic activity similar to the wildtype protein rLID1 while the rLID1_W protein has superior enzymatic activity. After that, it was performed a biological assay and mutant proteins were found to be capable of causing dermonecrosis, but the rLID1_W protein, in the concentration used, has much lower capacity than the wildtype protein. Our data indicates that the mutation on C-Terminal of rLID1 impacts both biological and enzymatic activity of the protein.